CONSTITUTIONAL TRANSPLANT IN THE PEOPLE’S REPUBLIC OF CHINA: THE INFLUENCE OF THE SOVIET MODEL AND CHALLENGES IN THE GLOBALIZATION ERA - J. Fan (BRICS Law Journal)
In this essay, I mainly focus on the constitutional transplantation in the People’s Republic of China. Firstly, I briefly present the Chinese constitution-making process from the Qing dynasty to the Republic of China to show that both regimes had transplanted more or less liberal constitutional principles, rules and institutions into their domestic constitutional document. Then, because China and the Former Soviet Union shared the Marxism-Leninism, China’s 1954 Constitution borrowed almost all the constitutional articles to various extents from the 1936 Soviet constitutional code. Though few articles of the 1977 Soviet Constitution have been imported into China’s present 1982 Constitution, China’s Constitution is still influenced by the Soviet model of constitution in many aspects related to the political and legal reform in the post-Mao era. Globalization brings many challenges to present-day China’s Soviet- featured constitutional system. With China’s accession to the WTO, a qualified judicial review mechanism is required to be established by the other Member States. However, China seems not to satisfy this obligation under the framework of the present legal system. In addition, a constitutional review mechanism is still absent in China. Besides, the modern Chinese legal system keeps silent on the domestic implementation of the UN international human rights treaties in view of the fact that Chinese international law theory was molded by Soviet’s which took highly concerned on protection of its state sovereignty. Chinese authorities, on the other hand, take a vague attitude to universal human rights standards. They sometimes prefer to observe them, while in other cases, they are not willing to follow them. Besides that, the domestic effects of international law also depend on the outcomes of the struggle and compromise between the reformist and Chinese Marxist conservative.